Nutritional Status of 6th-Year Students at Hanoi Medical University in 2022-2023 - Thi Phuong, Tran; Thi Hong Diem, Nguyen; Nhi Bac, Nguyen; Tung Son, Pham; Thi Minh Ngoc, Phan; Quang Dung, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2024)
Background: Final year medical students are one of the forces participating in future health care for the people. Therefore, their nutritional status is an issue worthy of concern and research. Objective: To assess the nutritional status of 6 th -year students at Hanoi Medical University in the 2022-2023 school year. Method: A descriptive cross-sectional study was conducted on 575 6 th -year students at Hanoi Medical University in the 2022 - 2023 school year from June to December 2023. Nutritional status was assessed by anthropometric methods, including measuring weight, height, waist circumference, and hip circumference, and evaluating nutritional status according to BMI and waist-to-hip ratio. Results: 72.5% of students had normal nutritional status, 14.4% of students were overweight-obese, 1.9% of students were obese (BMI ≥ 30), and 13.0% of students had chronic energy deficiency. The risks of overweight-obesity according to waist-to-hip ratio in male and female students were 6.8% and 2.2%, respectively. Conclusion: According to BMI, the majority of students had normal nutritional status, but there were also overweight, obese, and chronic energy deficiency students. Interventions need to be carried out to improve the nutritional status of students.